2022
DOI: 10.3390/cancers14081922
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial Cancer Management in Young Women

Abstract: Endometrial cancer (EC) rarely develops in young women. Most cases are associated with known risk factors: BMI > 30, history of Polycystic Ovary Syndrome (PCOs), and race differentiation. The molecular EC classification based on The Cancer Genome Atlas Research Network divides these heterogeneous cancers into four types: Polymerase Epsilon Mutation (POLE), Microsatellite Instability (MSI), Copy Number Low (CNL), and Copy Number High (CNH). This division was introduced to allow for early assessment of neopla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 69 publications
0
19
0
Order By: Relevance
“…The EC risk stratification used in the treatment approach has been based on histological types. In 1983, Bokhman was the first to distinguish two types of EC [ 6 ]. Stage assignment is generally more objective, but trials have shown large inconsistencies and disagreements in grade, histology type, stage, or risk factors based on stromal invasion, myometrial invasion, or lymphovascular invasion (LVI).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The EC risk stratification used in the treatment approach has been based on histological types. In 1983, Bokhman was the first to distinguish two types of EC [ 6 ]. Stage assignment is generally more objective, but trials have shown large inconsistencies and disagreements in grade, histology type, stage, or risk factors based on stromal invasion, myometrial invasion, or lymphovascular invasion (LVI).…”
Section: Resultsmentioning
confidence: 99%
“…While the precise mechanisms remain elusive, mutations in PTEN appear to influence cell cycle regulation, CTNNB1 mutations are associated with increased mobility and invasiveness, and mutations in PIK3CA (encoding the p110a catalytic subunit of PIK3) inhibit apoptosis. Furthermore, additional research has identified mutations in KRAS (Ki-ras 2 Kirsten rat sarcoma viral oncogene homolog), LOH (loss of heterozygosity), and BRAF (B-Raf murine sarcoma viral oncogene homolog B) within endometriotic lesions [ 1 , 3 , 6 , 11 , 16 ]. Additionally, endometriosis is recognized as a multifactorial disease, with evidence suggesting significant dysregulation of micro-RNA expression, mirroring its crucial role in cancer development [ 1 , 11 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations